Impact of Job Resources on Employee Green Behavior: An Empirical Investigation Among Employees Work in The Tourist Companies in Erbil- City Kurdistan Region of Iraq - Faeq, Dalia Khalid; Abdulla, Daroon Faraidoon; Ali, Bayad Jamal; Akoi, Shwana (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The aim of the current study was to look at job resources manifested by ( supervisor support and co-worker support) as a deciding factor in employees’ green behaviour in private businesses of tourist companies in Erbil- Kurdistan region –Iraq. The current study used a quantitative analysis approach in which a questionnaire was adapted from academic sources. The researchers distributed 250 questionnaires, but only 235 were returned. In order to achieve the objectives of the study and answer the question the researchers adopted a hypothetical construct reflecting the nature of the correlation and influence relationships between the variables of the study, based on a number of hypotheses which were subjected to a series of statistical tests through the (SPSS Vr. 24), and the results revealed that hypotheses are supported as the independent variable ( job resources) has a strong positive affect on a dependent variable ( employee green behaviour). Based on the conclusions, the current study provides number of recommendations such as: managers in tourist companies should properly evaluate employee green behavior, and depend on it for promotional opportunities, payments, and reward, for employees to be encouraged and motivated to participate in green activities in their workplace.